Temporal Trends, Socio-Economic Inequalities in Obesity and Responses by Federal Government, Nepal: A Systematic Review of Observational Studies, Policies, Strategies and Plans, 2005-2019 - Bhurtyal , Ashok; Adhikari , Dushala (Journal of Institute of Medicine Nepal, 2023)
Introduction Obesity has risen to epidemic proportions in low-income countries like Nepal, where maternal and child under-nutrition has reduced steadily. However, synthesised evidence on transition to obesity remains unavailable. We assessed trends and disparities in obesity occurrence, and examined central government’s policies and programmes. Methods We searched PubMed and Google Scholar for articles published between January 1, 2005 and April 10, 2019, and websites of Demographic and Health Survey, Non- Communicable Diseases Risk Factor Survey, and Micronutrient Status Survey. We synthesised obesity and overweight prevalence data from the selected studies, narratively; and disaggregated latest proportions from nation-wide surveys by gender, geographical location and household wealth quintile. We charted obesity related actions from policies, strategies and plans; obtained through the websites of health ministry and government’s planning commission. Results Twenty studies with data from 79,082 men and women aged 15 years or more and 11,866 children under five years, were included. Obesity or overweight among men and women increased from 20.0% in 2004 to 36.1% in 2016. Obesity alone rose from 5.3% to 7.5%. National average prevalence of childhood obesity or overweight remained very low. Overweight and obesity were more common among women, inhabitants of urban areas and central provinces, and the affluent. Governmental policies, strategies and plans on nutrition were primarily designed to control under-nutrition, with implications for preventing obesity. Conclusions Overweight and obesity increased substantially between 2005 and 2019, disproportionately affecting socio-economic and geographical groups. Governmental nutritional strategies should consider addressing obesogenic environments.